The Innovation of Visual Communication Thinking Mode Applied to Computer Graphics: from the Perspective of CAD Design - Wang, Haodong; Wang, Xiujun (International Conference on Intelligent Computing and Control Systems (Online), 2022)
This article combines computer digital graphics with visual communication design to meet diversified design requirements, which can maximize the level of innovation in visual communication design work. And the de velopment of CAD technology to the current stage of the application and innovation of visual communication design, and based on CAD design to conduct in-depth image mining of visual communication in computer graphics, and try to point out that the development of 3G communication technology is bringing a new round of revolution to the design world.